Nurses' Experiences of Caring for Patients with COVID-19: A Qualitative Study. (December 2022) - Almomani, Maysa H.; Khater, Wejdan A.; Akhu-Zaheya, Laila M.; Alloubani, Aladeen; AlAshram, Safa A.; Azab, Mohammed; Al-malkawi, Adeeb K.
The purpose of this study was to explore nurses' experiences, abilities, and willingness to care for patients with Coronavirus Disease 2019 (COVID-19). A descriptive qualitative study was conducted among 12 nurses working with patients with COVID-19. Purposive sampling was used to recruit participants from two national hospitals in Jordan. Semi-structured interviews (45–90 minutes each) with open-ended questions were held via Zoom to collect data. Four major themes emerged from the data analysis. The first theme, uncertainty, consisted of two subthemes: new experience and lack of training. The second theme was related to social stigma by society and other staff members. The third theme of front-line fighters consisted of two subthemes: empowering the main health caregiver and community acknowledgment. The fourth theme was related to challenges and consisted of two subthemes: physical and psychological challenges. At the beginning of the outbreak of COVID-19, the nurses had experienced a lack of certainty, physical and psychological challenges, and social stigmatization, which had negatively affected their willingness and ability to fight the outbreak. However, the nurses reported growing professionally and psychologically with time and becoming more knowledgeable, skillful, powerful, and confident care providers during the pandemic. Being able to fulfill their responsibilities and being acknowledged by others gave the nurses a sense of achievement. Early education and training about COVID-19, clear infection control protocols and guidelines, psychological counseling, and adequate social support are essential steps for enhancing nurses' mental well-being and willingness and ability to fight COVID-19.